Madu sebagai Terapi Komplementer untuk Anak dengan Diare Akut - Rokhaidah, Rokhaidah (Jurnal Kesehatan Holistic, 2019)
Abstract Diarrhea is an endemic disease in Indonesia which has the potential to become an Extraordinary Event (KLB) which is often accompanied by death. Handling diarrhea in addition to using pharmacotherapy techniques there are also complementary therapies that can be used, namely honey therapy. Benefits of honey to overcome diarrhea due to its antibacterial effect and its digestible nutritional content. Honey also helps in replacing body fluids lost due to diarrhea. The purpose of this study was to analyze the effect of honey on acute diarrhea in children under 5 years of age. The research method used was quasi experimental with pretest and posttest non equivalent control group design. The hypothesis of this study is that there are honeycomb influences on bowel frequency and fecal characteristics in children under 5 years of age with acute diarrhea. The results of this study showed a significant difference in frequency of bowel movements and stool consistency before and after giving honey (p value = 0.001) so It can be concluded that honey affects the frequency of bowel movements and stool consistency in children under five with acute diarrhea Keywords: acute diarrhea, children under 5 years, honey